Experimental investigation on noise characteristics of small scale vertical axis wind turbines in urban environments. (November 2022) - Li, Shoutu; Chen, Qin; Li, Ye; Pröbsting, Stefan; Yang, Congxin; Zheng, Xiaobo; Yang, Yannian; Zhu, Weijun; Shen, Wenzhong; Wu, Faming; Li, Deshun; Wang, Tongguang; et al.
Abstract: Noise pollution from wind turbines has been receiving significant attention with the rapid increase in global wind power installation, especially in urban environments where population density is high. Several countries tried to quantify the relation between wind turbine design characteristics and noise impact levels. To date, no quantitative results have been presented, while it is believed that the vertical axis wind turbine has advantages compared to horizontal axis wind turbines in certain applications. With the purpose to enhance understanding of noise pollution caused by vertical axis wind turbines in the urban environment, a systematic experimental test campaign in an anechoic wind tunnel was conducted. The results demonstrate that low-frequency noise increasingly affects humans when the wind speed increases. The blade-passing frequency is identified as a major parameter in the generation of low-frequency noise. More importantly, the noise pollution from various designs is discussed to analyze the impacts on humans and various animals. These designs are analyzed according to national standards from different countries. It is found that an optimal design of a vertical axis wind turbine is suitable for the urban environment with minimal noise impact. Highlights: Noise of vertical axis wind turbines is studied experimentally in a systematic way. The impact level of low-frequency noise increases as the wind speed increases. The blade-passing frequency is a major parameter in the low-frequency noise. Optimal design philosophies are recommended based on different urban environments.